Exploration on UV-Blocking Performance of Lignin from Palm (Trachycarpus Fortunei) Fiber - Yanlai Wang; Xiuyun Xiao; Shu Wang; Kang Li; Ying Jiang; Yifa Ma; Tonghua Zhang; Ruilong Ran (Journal of Natural Fibers, 2021)
To reveal the ultraviolet (UV) blocking mechanism of palm fiber, alkali lignin was extracted from palm and bamboo fiber and its UV absorption spectrum was tested, followed by some structural characterization. Palm fiber lignin was found to have a higher UV absorbance. Fourier Transform infrared spectroscopy (FTIR) analysis revealed that the ultraviolet absorbing functional groups in palm fibers including phenol OH, aliphatic OH, aromatic ring and triple bond structure. Thermogravimetric Analysis (TG) and elemental analysis indicated high protein content and highly concentrated aromatic structures also contribute to the superior UV absorption properties of palm fibers.